Overqualification as a Blunt Weapon on Productivity Improvement: Person-Job Fit Theory Integration - Maksum, Ikhsan; Fikriah, Nur Laili; Mayasari, Agatha (Institut Agama Islam Negeri Kendari, 2021)
Despite the growing number of studies that underlie the influence between perceived overqualification (POQ) and counterproductive behaviour (PKP), there is still a gap in the lack of research involving the role of affective mechanisms on the effect of POQ on PKP. In this study, researchers focused on the mediating role of job boredom (KTP) in the pathway of influence of POQ on PKP. Using a sample of 106 employees and lecturers at Islamic universities in Indonesia and using the integration of the theory of person-job fit, the researchers found that KTP fully mediates the effect of POQ on PKP.